Les représentations mentales - Claude Meyer (Communication)
In this article, the author proposes a discussion of the scientific legitimacy of mental representation and organizes his argument around the inherited theses of the quarrel of universality. In the first place, it is suggested that representation are the product of our understanding. And, the try to prove their existence in order to assure ourselves that they are indeed things. In concluding, the author ascertains that representation may indeed have no existence and are mere “emissions of the voice”. This text will also attempt a synthesis of what we know today about mental representations by questioning disciplines other than communication studies and try to suggest that this interdiscipline would do well to open itself up to the contributions of neuroscience and the cognitive sciences.